IMPROVING THE REASONING ABILITY OF ELEMENTARY SCHOOL STUDENT THROUGH THE INDONESIAN REALISTIC MATHEMATICS EDUCATION - Muhamad Saleh Ginting; Rully Charitas Indra Prahmana; Muhammad Isa; Murni Murni (Journal on Mathematics Education, 2018)
By taking the role as a mentor and a facilitator, a teacher in the 4th grade of elementary school needs to look at the condition of the students in the concrete thinking stage. Learning process needs to be adjusted such that the abstract objects in mathematics can be represented through concrete objects as a bridge to enter the knowledge that the students already had, especially for the material of fraction. This research aims to analyze the achievement and the improvement of students’ mathematics reasoning ability through the implementation of Indonesian realistic mathematics education (PMRI) approach. The research subject consisted of 51 students in the experiment group and 45 students in the control group which categorized into three levels (low, intermediate, and high). The result suggests that the achievement and the improvement of students’ reasoning ability in the mathematics learning using PMRI approach are better than the conventional learning.DOI: http://dx.doi.org/10.22342/jme.9.1.5049.41-54